Optimizing the Role of Classroom Teachers in Enhancing Students’ Learning Independence in Aqidah and Moral Education - Jannah, Raodatul; Saprin; Idris, Ridwan (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to examine the significant influence of the implementation of homeroom teachers’ core responsibilities on students’ learning independence in Aqidah and Akhlak among Grade XI students at MA DDI Takkalasi, Barru Regency. This research employed an ex post facto design. The population comprised all 51 Grade XI students at MA DDI Takkalasi, who were included as research participants. Data were collected using a structured questionnaire distributed to the respondents and subsequently analyzed through descriptive and inferential statistical techniques. The findings indicate that the implementation of homeroom teachers’ core duties accounts for 39% of the variance in students’ learning independence in Aqidah and Akhlak, while the remaining 61% is attributable to other factors not examined in this study. The observed contribution reflects an initial level of effectiveness in fostering students’ learning independence. Nevertheless, this influence can be further enhanced through the integration of additional supporting factors, which may provide a more comprehensive and meaningful learning experience. Moreover, systematic and targeted evaluation can assist students in identifying their strengths and areas for improvement, thereby increasing their motivation to develop greater learning independence. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh signifikan pelaksanaan tugas pokok wali kelas terhadap kemandirian belajar akidah akhlak peserta didik kelas XI di MA DDI Takkalasi Kabupaten Barru. Jenis penelitian adalah penelitian ex-post facto. Populasi sebanyak 51 di ambil dari seluruh kelas XI yang ada di MA DDI Takkalasi. Metode pengumpulan data yang digunakan yaitu angket atau kuesioner. Angket disebarkan kepada responden kemudian dianalisis menggunakan analisis deskriptif dan analisis statistik inferensial. Hasil penelitian menunjukkan bahwa pengaruh tugas pokok wali kelas terhadap kemandirian belajar akidah akhlak peserta didik kelas XI di MA DDI Takkalasi berkontribusi sebesar 39% dan sisanya sebesar 61% dipengaruhi oleh variabel lain yang tidak dimasukkan dalam penelitian ini. Pengaruh sebesar 39% telah mencerminkan keberhasilan awal dalam meningkatkan kemandirian belajar peserta didik. Namun, pengaruh ini masih dapat ditingkatkan dengan faktor lainnya, hal ini akan memberikan pengalaman belajar yang lebih kaya dan mendalam bagi peserta didik. Begitupun dengan evaluasi yang terarah, peserta didik dapat memahami kekuatan dan kelemahan mereka, sehingga lebih termotivasi untuk meningkatkan kemandirian belajar.